When families shape the self: The mediating role of self-esteem in the link between family functioning and loneliness - Erni Julianti Simanjuntak; Helsa Helsa; Allessandra Theresia (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2026)
Emerging adulthood is a period of transition and exploration during which, as individuals fulfill developmental tasks, they are vulnerable to experiencing loneliness. This study aims to investigate the mediating role of self-esteem on the association between family functioning and loneliness among emerging adults. This study used a quantitative correlational method and a cross-sectional approach with 139 participants aged 18-29 years. The instruments used in this study consisted of the General Functioning Subscale (FAD-GF), the UCLA Loneliness Scale, and the Self-esteem Scale. The study found that self-esteem acts as a mediator in the relationship between family functioning and loneliness. This finding explains how positively functioning families build higher individual self-esteem, thereby reducing loneliness in emerging adulthood. The implications of this study are expected to serve as a reference for creating psychoeducation or designing family relationship-based interventions by optimizing family function as a core community to increase individual self-esteem and reduce loneliness.